Changes Related to Age in Natural and Acquired Systemic Self-IgG Responses in Malaria - Dassé, Romuald; Lefranc, Didier; Dubucquoi, Sylvain; Dussart, Patricia; Dutoit-Lefevre, Virginie; Sendid, Boualem; Sombo Mambo, François; Vermersch, Patrick; Prin, Lionel (Interdisciplinary Perspectives on Infectious Diseases, 2011)
Background. Absence of acquired protective immunity in endemic areas children leads to higher susceptibility to severe malaria. To investigate the involvement of regulatory process related to self-reactivity, we evaluated potent changes in auto-antibody reactivity profiles in children and older subjects living in malaria-endemic zones comparatively to none-exposed healthy controls. Methods. Analysis of IgG self-reactive footprints was performed using Western blotting against healthy brain antigens. Plasmas of 102 malaria exposed individuals (MEIs) from endemic zone, with or without cerebral malaria (CM) were compared to plasmas from non-endemic controls (NECs). Using linear discriminant and principal component analysis, immune footprints were compared by counting the number, the presence or absence of reactive bands. We identified the most discriminant bands with respect to age and clinical status. Results. A higher number of bands were recognized by IgG auto-antibodies in MEI than in NEC. Characteristic changes in systemic self-IgG-reactive repertoire were found with antigenic bands that discriminate Plasmodium falciparum infections with or without CM according to age. 8 antigenic bands distributed in MEI compared with NEC were identified while 6 other antigenic bands were distributed within MEI according to the age and clinical status. Such distortion might be due to evolutionary processes leading to pathogenic/protective events.